ORDINAL LOGISTIC REGRESSION MODEL FOR HUMAN DEVELOPMENT INDEX DATA IN PAPUA AND WEST PAPUA PROVINCES - Nabilla Rida Tri Nisa; Novia Amilatus Solekha; Abdullah Fahmi; Panji Jilblathar; Purhadi Purhadi (Jurnal Statistika Universitas Muhammadiyah Semarang, 2024)
The Human Development Index (HDI) is a key indicator used to measure the quality of economic development, particularly the degree of human development. In 2019, the HDI for Papua Province was 60.84, while West Papua Province recorded a value of 64.70. According to the Central Statistics Agency, these figures indicate that Papua and West Papua are the provinces with the lowest HDI in Indonesia. This research aims to identify the factors influencing the HDI in Papua and West Papua Provinces in 2019 using an ordinal logistic regression approach. The study utilizes secondary data from the Central Statistics Agency for both provinces. The results indicate that the model developed is appropriate, with the Open Unemployment Rate (TPT) and average per capita expenditure being significant factors influencing HDI. The model's effectiveness is evidenced by an Akaike Information Criterion (AIC) value of 28.978